Effect of Exchange Rate and Inflation Rate on The Index of Property in Indonesia in Year 2013 May-2017 June - Nurul Aidha, Cut; Haposan L Tobing, Posma (Cv. Syntax Corporation Indonesia, 2019)
Improved economic development after the crisis period, along with improved political and security conditions are conducive conditions for the development of the property industry. The improvement in economic conditions is reflected in macroeconomic indicators such as lower inflation rate and relatively stable exchange rate compared to the 1998 crisis period. Starting from 2003, the growth rate of property sector began to show improvement after the crisis development. This research aims to analyze the effect of exchange rate and inflation rate on the index of property in Indonesia. The data used are time series of quantitative secondary data obtained from the BPS during the period 2013 May until 2017 June. Regression model used is the method of multiple linear regression analysis. Based on the results of tests per out formed with simultaneous test (F test) show that overall the independent variables (Exchange Rate and Inflation Rate) have a significant effect on the index of property in Indonesia. The value of R2 amounting 0.467 which means exchange rate and inflation rate explanatory 46.7 percent of index property, while the rest of 53.3 percent is explained by other variables outside of the used model.